Las Memorias de Gonzalo Fernández de Oviedo : Volumen II - Fernández de Oviedo y Valdes, Gonzalo, 1478-1557 (University of North Carolina publications of the Department of Romance Languages., 2019)
This is an edition of the parts of the Quincuagenas of Gonzalo Fernandez de Oviedo that the author considers "aspectos de las Quincuagenas que podemos considerar respaldados por las vivencias del autor," hence the title Memorias. We are left, however, with two substantial volumes of which this is the second.